Question
upstudy study bank question image url

\( (x+2)^{\frac{1}{2}}=x \) What is the solution to the given equation?

Ask by Morrison Bond. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The solution to the equation \( \sqrt{x + 2} = x \) is \( x = 2 \).

Solution

To solve the equation: \[ \sqrt{x + 2} = x \] **Step 1: Determine the Domain** The square root function requires the argument to be non-negative: \[ x + 2 \geq 0 \implies x \geq -2 \] Additionally, since \(\sqrt{x + 2} = x\) and the square root is always non-negative, \(x\) must also satisfy: \[ x \geq 0 \] So, the domain of the equation is \(x \geq 0\). **Step 2: Square Both Sides** To eliminate the square root, square both sides of the equation: \[ (\sqrt{x + 2})^2 = x^2 \implies x + 2 = x^2 \] **Step 3: Rearrange the Equation** Bring all terms to one side to form a quadratic equation: \[ x^2 - x - 2 = 0 \] **Step 4: Solve the Quadratic Equation** Use the quadratic formula: \[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \] For the equation \(x^2 - x - 2 = 0\), \(a = 1\), \(b = -1\), and \(c = -2\). Plugging these in: \[ x = \frac{-(-1) \pm \sqrt{(-1)^2 - 4(1)(-2)}}{2(1)} = \frac{1 \pm \sqrt{1 + 8}}{2} = \frac{1 \pm 3}{2} \] This gives two potential solutions: \[ x = \frac{1 + 3}{2} = 2 \quad \text{and} \quad x = \frac{1 - 3}{2} = -1 \] **Step 5: Verify the Solutions** Recall the domain \(x \geq 0\): - \(x = 2\) is valid. - \(x = -1\) is **not** valid since it doesn't satisfy \(x \geq 0\). **Conclusion** The only real solution to the equation is: \[ \boxed{2} \]

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

The Deep Dive

To solve the equation \( (x+2)^{\frac{1}{2}}=x \), first, square both sides to eliminate the square root, yielding \( x + 2 = x^2 \). Rearranging this gives the quadratic equation \( x^2 - x - 2 = 0 \). Factoring, we find \( (x - 2)(x + 1) = 0 \), giving solutions \( x = 2 \) and \( x = -1 \). However, we must check these in the original equation due to potential extraneous solutions. When substituting \( x = 2 \), we find \( (2+2)^{\frac{1}{2}} = 2 \), which holds true. For \( x = -1 \), \( (-1+2)^{\frac{1}{2}} = 1 \), which does not equal \(-1\). Thus, the only valid solution is \( x = 2 \). In summary, the solution is \( x = 2 \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy